Spatial Drought Assessment Using Geospatial Techniques In A Semi Arid Region - Dhasarathan Rajendran, Gajendran Chellaiah (International Journal of Advanced Science and Technology, 2020)
Water is a vital component of the hydrological cycle and is important for the sustainability of streams, lakes, wetlands and aquatic structures. Drought-monitoring has been based only on observation of weather stations, lacking the spontaneous spatial coverage to monitor the drought conditions. The objective of this research was to use GIS-based techniques to classify the drought conditions in a semi-arid zone. Normalised Difference Vegetation Index offers an ideal method for finding land use, vegetation index, and water bodies with few distant sensed information band combinations. The Drought Index has been derived for Coimbatore district and the drought-affected areas were identified. Thus, helps to identify the agricultural and hydrological drought prone zone in the study area. A spatial map was created to represent dry areas with three classifications of water content namely low, moderate and high. It was found that 75% of the Coimbatore district has moderate water content and 21% of the Coimbatore district has very good water content.